Embedded prayer time system using GPS module - Che Muhammad Nor, Che Isa (Universiti Malaysia Perlis, 2008)
This final year project is about to calculate of prayer time system in microcontroller using the spatial data retrieve from satellite via Global Positioning System (GPS) receiver module. This system is able to determine the position of latitude and longitude of the earth. For this project, a complete set of DS89C450 microcontroller board is developed. The microcontroller work to calculate the five prayer time Fajr, Zuhr, Asr, Maghrib and Isha. The calculation is performed using C language programming. Then it is need to embed into the DS89C450 microcontroller. The microcontroller board will be connected to the GPS Receiver Module to get the latitude and longitude as the input data. Then the microcontroller calculates the prayer time and the result will be displayed through Liquid Crystal Display (LCD). The aim of this project is to make sure the prayer time will be displayed via Liquid Crystal Display and it will occur automatically without any manually load position into the microcontroller.